Ministry of Natural Resources - Buganda Government
This file contains minutes and correspondence, 1963-1965, papers on war against attrocities of 1964, estimates for the Ministry of Natural Resources, 1964-1966.
AR/BUG/1/5
English
Shelf no. 1